2023
DOI: 10.55951/nurture.v17i1.137
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between internet usage and technostress: A moderated mediation model

Abstract: Purpose: Technostress or technology-induced stress is well-known in the literature among working people. Although technology is becoming more prevalent in higher education, there is still a lack of research investigating the predictors of technostress and its impact on university students. The current study explored: (i) the mediating role of problematic internet use (PIU) in the relationship between internet usage and technostress and (ii) the moderation of personality type on the relationship between interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We found a significant positive correlation between technostress and IA which shows that technostress increases the arousal of people to use internet-connected devices that further increases the stress level of people as found by the previous studies. 57,108 The results also demonstrate that technostress does not directly influence the QoL. The possible reason for this result may be that some people may feel anxiety in online activities, whereas other users may find relief from the use of internet-linked devices.…”
Section: Discussionmentioning
confidence: 81%
“…We found a significant positive correlation between technostress and IA which shows that technostress increases the arousal of people to use internet-connected devices that further increases the stress level of people as found by the previous studies. 57,108 The results also demonstrate that technostress does not directly influence the QoL. The possible reason for this result may be that some people may feel anxiety in online activities, whereas other users may find relief from the use of internet-linked devices.…”
Section: Discussionmentioning
confidence: 81%
“…At the second stage of the study, the idea was experimentally implemented that it is possible to increase the level of students' interest in aquaculture, in general, as well as in its objects and products, if the didactic potential of a computer game is actively used [6]. An analysis of modern foreign practice of implementing gaming technologies in the educational process has shown that in European countries [7] and in the countries of the Arab East, didactic material in printed form has been accumulated [8], and thematic computer games have been developed and actively used [9,10,11]. They, as it seems at first, do not represent the most popular branch of animal husbandry [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Science and technology governance and technology-focused ethics discussions have as one goal to decrease the appearance of new social stressors and to decrease the presence of already existing social stressors as a consequence of scientific and technological advancements [39]. The term technostress reflects technology-induced stress [99][100][101][102][103][104][105][106]. It is argued that more studies are needed that link social stress to the automation literature [71].…”
Section: Social Stressors and Science And Technologymentioning
confidence: 99%
“…It is well known that technologies can cause stress. The term technostress was coined to flag technology-based stress [99][100][101][102][103][104][105][106]. It is argued that more studies are needed that link social stress and automation literature [71].…”
Section: Science and Technology Governance And Ethics And Stress* And...mentioning
confidence: 99%